Anesthesiologists' knowledge about packed red blood cells transfusion in surgical patients - Soares,Joyce Mendes (2017)
Abstract Introduction Blood is an important resource in several lifesaving interventions, such as anemia correction and improvement of oxygen transport capacity. Despite advances, packed red blood cell (PRBC) transfusion still involves risks. The aim of this study was to describe the knowledge of anesthesiologists about the indications, adverse effects, and alternatives to red blood cell transfusion intraoperatively. Method Cross-sectional study using a questionnaire containing multiple choice questions and clinical cases related to relevant factors on the decision whether to perform PRBC transfusion, its adverse effects, hemoglobin triggers, preventive measures, and blood conservation strategies. The questionnaire was filled without the presence of the investigator. Likert scale was used and the average rank of responses was calculated. The Epi Info 7 software was used for data analysis. Results 79% of the institution's anesthesiologists answered the questionnaire; 100% identified the main adverse effects related to blood transfusion. When asked about the factors that influence the transfusion decision, hemoglobin level had the highest agreement (MR = 4.46) followed by heart disease (MR = 4.26); hematocrit (MR = 4.34); age (RM = 4.1) and microcirculation evaluation (MR = 4.22). Respondents (82.3%) identified levels of Hb = 6 g.dL-1 as a trigger to transfuse healthy patient. Regarding blood conservation strategies, hypervolemic hemodilution (MR = 2.81) and decided by drugs (MR = 2.95) were the least reported. Conclusion We identify a good understanding of anesthesiologists about PRBC transfusion; however, there is a need for refresher courses on the subject.